2020
DOI: 10.1073/pnas.1906507117
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence for quasi-equilibrium chemistry in thermally mature natural gases

Abstract: Natural gas is a key energy resource, and understanding how it forms is important for predicting where it forms in economically important volumes. However, the origin of dry thermogenic natural gas is one of the most controversial topics in petroleum geochemistry, with several differing hypotheses proposed, including kinetic processes (such as thermal cleavage, phase partitioning during migration, and demethylation of aromatic rings) and equilibrium processes (such as transition metal catalysis). The dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…The carbon isotopic composition of thermogenic methane is generally thought to be controlled by kinetic isotope effects (e.g., Tang et al, 2000) However, Smith et al (1998) showed experimentally that the thermal decomposition of acetic acid yields CO 2 and methane with carbon isotopic compositions consistent with generation in carbon isotopic equilibrium from 290 to 650°C. Most recently, based on observed differences between the  13 C of CO 2 and thermogenic methane vs. measured methane clumped-isotope based temperatures, Thiagarajan et al (2020) proposed that thermogenic methane and CO 2 can achieve carbon isotopic equilibrium in the subsurface through reactions that promote methane oxidation and CO 2 reduction.…”
Section: The Role Of Isotopic Equilibrium In Setting the Isotopic Composition Of Methanementioning
confidence: 99%
See 2 more Smart Citations
“…The carbon isotopic composition of thermogenic methane is generally thought to be controlled by kinetic isotope effects (e.g., Tang et al, 2000) However, Smith et al (1998) showed experimentally that the thermal decomposition of acetic acid yields CO 2 and methane with carbon isotopic compositions consistent with generation in carbon isotopic equilibrium from 290 to 650°C. Most recently, based on observed differences between the  13 C of CO 2 and thermogenic methane vs. measured methane clumped-isotope based temperatures, Thiagarajan et al (2020) proposed that thermogenic methane and CO 2 can achieve carbon isotopic equilibrium in the subsurface through reactions that promote methane oxidation and CO 2 reduction.…”
Section: The Role Of Isotopic Equilibrium In Setting the Isotopic Composition Of Methanementioning
confidence: 99%
“…Additionally, proposed that thermogenic methane may form in (or achieve) hydrogen isotopic equilibrium with water based on the observed agreement between apparent methane clumpedisotope temperatures (from 118-204°C) and measured differences in the D of methane and water versus those expected for CH 4 -H 2 O hydrogen isotopic equilibrium. Most recently, Thiagarajan et al (2020) proposed that methane equilibrates hydrogen with other gaseous alkanes (e.g., ethane, propane, etc.) in thermogenic gas reservoirs.…”
Section: The Role Of Isotopic Equilibrium In Setting the Isotopic Composition Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…This could reflect similarities between methane and propane in the mechanisms and kinetics of carbon-bound hydrogen equilibration. This could reflect the ability of both to undergo catalystmediated exchange or that they are both participants in radical chain reactions that allow interconversion of molecules and radicals and exchange of atoms (Xia and Gao, 2018;Thiagarajan et al, 2020b).…”
Section: Exchange and Equilibrationmentioning
confidence: 99%
“…Wang et al, 2015;Young et al, 2017;Douglas et al, 2017;Stolper et al, 2018;Giunta et al, 2019). This discrepancy could be taken as evidence for an alternative hypothesis that catagenetic reactions proceed through locally reversible metastable equilibria (Helgeson et al, 2009;Mango et al, 2009;Thiagarajan et al, 2020b). Alternatively, like interpretations of some natural microbial methane, thermogenic methane might be produced by irreversible, kinetically controlled reactions, but subsequently driven to equilibrium by some more reversible chemical process.…”
Section: Introductionmentioning
confidence: 99%